Amperometric Biosensor for Continuous Monitoring Irgarol 1051 in Sea Water. Issue 8 (25th May 2016) - Salvador, J.‐Pablo; Marco, M.‐Pilar
Abstract: Irgarol 1051 is one of the most employed antifouling agents and is one of the most commonly found in marine environment. According to its widespread use the European Comission turned its attention on this agent as one of the priority substances that has to be controlled. The aim of this article is to develop an immunosensor for the determination of Irgarol 1051 in sea water for implementation in a flow analysis system. The transducing principle employed for its development was an amperometric detection using gold screen printed electrodes which were functionalized for the covalent immobilization of the immunoreagents. The detection of Irgarol 1051 was performed using specific antibodies working under competitive indirect format. The immunosensor was demonstrated to measure directly in sea water with high detectability, accurately and robust. The system allows consecutive measurements using the same chip owing to an easy regeneration process. The limit of detection reached was 0.15±0.09 nM (0.038±0.022 µg ⋅ L −1 ) measured directly in sea water. Abstract :